The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4236/ojfd.2015.54032
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Vortex Structures in Obliquely Rotating Fluid

Abstract: In this paper, we find a new large scale instability which appears in obliquely rotating flow with the small scale turbulence, generated by external force with small Reynolds number. The external force has no helicity. The theory is based on the rigorous method of multi-scale asymptotic expansion. Nonlinear equations for instability are obtained in the third order of the perturbation theory. In this article, we explain in detail the nonlinear stage of the instability and we find the nonlinear periodic vortices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 10 publications
7
20
0
Order By: Relevance
“…In the case of non-electroconductive fluid ( = 0)  with the temperature gradient ( 0) T   we obtain the same results as in [50]. In the limit of non-electroconductive ( = 0)  and homogeneous fluid ( =0) T  we obtain the results of [46]. To study this dynamo model, it is necessary at first to consider the evolution of small perturbations and then to examine the nonlinear effects.…”
Section: Equations For Large-scale Fieldssupporting
confidence: 64%
See 3 more Smart Citations
“…In the case of non-electroconductive fluid ( = 0)  with the temperature gradient ( 0) T   we obtain the same results as in [50]. In the limit of non-electroconductive ( = 0)  and homogeneous fluid ( =0) T  we obtain the results of [46]. To study this dynamo model, it is necessary at first to consider the evolution of small perturbations and then to examine the nonlinear effects.…”
Section: Equations For Large-scale Fieldssupporting
confidence: 64%
“…The development of this large-scale instability in obliquely rotating fluid gives rise to nonlinear large-scale helical structures of Beltrami vortex type, or to localized kinks with internal helical structure. In [47] the new hydrodynamic  -effect found in [46] was generalized to the case of electroconductive fluid. The corresponding large-scale instability leads to the generation of LSVS and magnetic fields.…”
Section: Eejp 1 (2020)mentioning
confidence: 98%
See 2 more Smart Citations
“…Obviously, the question arises of the possibility of the generation of large-scale vortex fields in a rotating media under the influence of small-scale forces with zero helicity. An example of the generation of LSVS in a rotating incompressible fluid was found in [21]. It was also shown that the expansion of a large-scale instability in an inclined rotating fluid generates nonlinear large-scale helical vortex structures or localized Beltrami vortices within the internal helical structure.…”
Section: Introductionmentioning
confidence: 96%